Importancia de la auditoría forense caso de corrupción contable: Saludcoop (2021)
The present investigation called: "Importance of Forensic Audit: Accounting corruption case: Saludcoop", which aims through its main objective to evaluate the importance of forensic audit in the case of accounting corruption: SaludCoop, which for its development is They include theories, concepts and legal framework that support it. A deep documentary and bibliographic review of the subject is framed, therefore, as a primary research source, an analysis of the Forensic Audit Report made by the Comptroller General of the Nation of November 2016 will be carried out, and additionally as a secondary investigation source the ruling of file 25000-23-41-000-2014-01442-00 and extensive reports, interviews, articles, news, about the case, as well as the search for the various states of the art that deal with the matter necessary to substantiate the study problems from the field of forensic audit, crimes, fraud or corruption, in addition to the current regulations that govern this investigation framed in the field of public accounting, forensic audit, EPS, among others, in order to identify the fraud that led to an event of corruption the acts incurred by the entity.